Prevalence of Human Papillomavirus (HPV) Genotypes in Cervicovaginal Secretions of Human Immunodeficiency Virus (HIV) Positive Indian Women and Correlation With Clinico-Virological Parameters - Lall, Mahima; Dar, Lalit; Bhatla, Neerja; Kumar, Pankaj; Choudhary, Aashish; Mathur, Sandeep R.; Gupta, Rajiv M. (Frontiers in Reproductive Health, 2021)
Introduction and Background: Both human papillomavirus (HPV) and the human immunodeficiency virus (HIV) are sexually transmitted. High-risk (HR) HPV types are a causal factor in cervical cancer. Persistent HPV infection in this subset of immunocompromised women results in faster disease progression. The study determined the prevalence of HPV genotypes in cervicovaginal secretions of HIV seropositive women and the correlation with CD4 counts and cytology. Method: One hundred, non-pregnant, HIV-positive women of 18 years of age and above were enrolled in this cross-sectional study following approval by the institutional ethical committee. A written consent, questionnaire, followed by sample collection including a Papanicolaou (Pap) smear for cytology was undertaken. Cervicovaginal secretion samples were collected in the Digene® specimen transport medium (STM) (Qiagen Gaithersburg Inc., MD, USA). HPV genotyping was carried out with PCR amplification of a 65-base pair (bp) fragment in the L1 region of the HPV genome using the short PCR fragment (SPF10) primers followed by reverse hybridization by line probe assay (LPA) using the INNOLiPA HPV Genotyping Extra kit (Fujirebio, Belgium). Quantitation of HPV-16 and−18 viral loads (VLs) was done by real-time PCR. Results of Pap smear cytology were correlated with CD4 counts and HPV-16 and−18 VLs. Results: Mean age of the subjects was 34.9 years ± 7.2 years (median 33.0 years, range 24–60 years). HPV was detected in 62 of 93 (66.6%) samples. Twenty (32.25%) of these 62 samples harbored a single HPV genotype. Multiple genotypes (more than two) were detected in 38 (61.3%) samples. HPV-16 was the commonest genotype detected in 26 (27.9%) of all samples and 41.9% of HPV positive samples. Pap smear cytology was reported for 93 women included in the study. Women who had normal cytology were reported as negative for intraepithelial malignancy or lesion (NILM; n = 62; 71.36%), two women had a high-grade squamous intraepithelial lesion (HSIL), low-grade squamous intraepithelial lesion (LSIL; n = 11), atypical squamous cells of undetermined significance (ASCUS; n = 12). Those smears with inadequate material were reported as scant (n = 6). The median CD4 count was 363/cu.mm (range 39–787) in HPV-positive women compared to 423/cu.mm (range 141–996) in those HPV-negative women. Quantitation of HPV-16 and−18 VL was done in duplicate for samples positive by PCR reverse hybridization (INNOLiPA). Of these 20 samples (65%), 12 samples were positive by real-time PCR. The normalized HPV-16 VL ranged between 18 and 240,000 copies/cell. The normalized HPV-18 VL in cervical samples ranged between ~24 and 60,000 copies/cell. Conclusion: HIV-positive women may be infected with multiple genotypes other than HPV-16 and−18. This may have implications on the vaccines available currently which target few specific genotypes only. Studies are required to determine the predictive role of HR HPV genotypes, in significant copy numbers especially in HIV seropositive women. It would be clinically relevant if the HPV VLs, cervical cytology, and CD4 counts are considered into cervical cancer screening programs for triage and follow-up of these women.